การจัดการเรียนรู้โดยใช้หนังสืออิเล็กทรอนิกส์ร่วมกับเกมการแข่งขันสะกดคำวิชาภาษาไทย เพื่อพัฒนาทักษะการเขียนสะกดคำของนักเรียนชั้นประถมศึกษาปีที่ 4 - Lopchang, Peerapha; Ongardwanich , Namthip (Journal of Graduate School Sakon Nakhon Rajabhat University, 2022)
The purposes of this research were to 1) develop learning management on the topic of the consonant rules using e-books with Thai spelling games for Pratomsuksa 4 students, 2) compare word-spelled writing skills on the consonant rules for Pratomsuksa 4 students before and after the intervention, and 3) compare Pratomsuksa 4 students’ word-spelled writing skills on the consonant rules after the intervention to the 70 percent criteria. The sample, obtained through purposive sampling, included 10 students in Pratomsuksa 4 studying at Wat Ban Mai School in the second semester of the academic year 2020. The research instruments were 1) an e-book on the topic of consonant rules, 2) nine lesson plans, and 3) a 30- item test on word-spelled writing skills with the reliability of 0.88. The research results were as follows 1) the developed learning management using e-books with Thai spelling games for Pratomsuksa 4 students had an efficiency at the highest level ( = 4.73, S.D. = 0.16), word-spelled writing skills of Pratomsuksa 4 students before and after the intervention were at the 0.05 level of significance, and 3) The word-spelled writing skills of Pratomsuksa 4 students after the intervention were higher than the defined criterion of 70 percent at the .05 level of significance.